2018
DOI: 10.1021/acssuschemeng.8b02119
|View full text |Cite
|
Sign up to set email alerts
|

Designing Ionic Liquids with Dual Lewis Basic Sites to Efficiently Separate Phenolic Compounds from Low-Temperature Coal Tar

Abstract: Although separation of phenolic compounds from coal tar has a good practical application value in industry, the traditional separation method can result in serious environmental problems. In the present work, three ionic liquids (ILs) with dual Lewis basic sites were designed and synthesized by neutralizating 1,1,3,3-tetramethylguanidine (TMG) and corresponding acids (L-proline, acetate acid, and tetrafluoroboric acid), which were employed to separate phenolic compounds from the model oil and coal tar. The bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Figure shows the FT‐IR spectrum of DBILs in the range 400–4000 cm −1 .From Figure , there was an obvious peak around 1628 cm −1 in the spectrum of all DBILs, due to typical characteristic peak of C=N species in DBU ring. The peak in the range of 2857–2292 cm −1 was ascribed to the stretching vibration of saturated C‐H in alkyl chains . The peak in the range of 2853–2930 cm −1 was related to the stretching vibration of C‐H in methylene.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure shows the FT‐IR spectrum of DBILs in the range 400–4000 cm −1 .From Figure , there was an obvious peak around 1628 cm −1 in the spectrum of all DBILs, due to typical characteristic peak of C=N species in DBU ring. The peak in the range of 2857–2292 cm −1 was ascribed to the stretching vibration of saturated C‐H in alkyl chains . The peak in the range of 2853–2930 cm −1 was related to the stretching vibration of C‐H in methylene.…”
Section: Resultsmentioning
confidence: 98%
“…The peak in the range of 2857-2292 cm −1 was ascribed to the SCHEME 1 Synthesis process and molecular structure of [BDBU]Br SCHEME 2 Synthesis process and molecular structure of stretching vibration of saturated C-H in alkyl chains. [10] The peak in the range of 2853-2930 cm −1 was related to the stretching vibration of C-H in methylene. The broad peak absorption band at ca.…”
Section: Synthesis Process Of the Dbilsmentioning
confidence: 99%
“…As shown in Figure 7 , the peak at 3497.90 cm –1 is ascribed to −OH in pure m -cresol, whereas the peaks at 3451.39 and 3445.56 cm –1 are ascribed to −NH 3 + in the pure ILs [PA][FA] and [PA][Ac], respectively. 6 When the complexes formed, the characterization peak shifted to 3438.51 cm –1 for complex 1 ([PA][FA] + m -cresol) and shifted to 3438.32 cm –1 for complex 2 ([PA][Ac] + m -cresol), which indicated that hydrogen bonds were formed between m -cresol and the ILs.…”
Section: Intermolecular Interaction Mechanism Exploration By Fouriermentioning
confidence: 99%
“…In addition, more results of separating phenolic compounds using ILs as extractants were reported in the literature. 6 , 27 29 To our knowledge, m -cresol has the highest content (13.41 wt %) in phenol oil from low-temperature coal tar, 30 but fewer literature studies have reported the separation of m -cresol as a representative phenolic compound from model oil since phenol or p -cresol is usually selected as the typical phenolic compound. 6 , 21 , 31 33 Hence, it is meaningful to explore the separation of m -cresol from LTCT by means of ionic liquids.…”
Section: Introductionmentioning
confidence: 97%
“…They are being applied in the fields of synthesis, separations, catalysis and electrochemistry. 1216 ILs have also shown potential for safely storing halogens by forming trihalide or polyhalide anions, such as [Cl 3 ] − , [Br 3 ] − , [I 3 ] − or [ClBr 2 ] − . 1720 Recently, trichloride ILs have been synthesized and used for dissolution of various metals and alloys at mild conditions.…”
Section: Introductionmentioning
confidence: 99%